Assessing the availability of trusted health information in a rural Appalachia community using social network analysis. Issue 3 (March 2023) - Smalls, Brittany L.; Eddens, Katherine; Kruse-Diehr, Aaron; Williams, Edith; Ortz, Courtney L.
Abstract: The purpose of this study was to investigate how trusted health information is transmitted within a rural Appalachian community. Egocentric social network methods were used to identify and characterize influential community members ("alters") that participants ("egos") go to for trusted health advice. Friends and "other health professionals" were named most frequently as health advice alters, and health advice was described as frequent and helpful. Participants could count on their health advice network for multiple forms of social support. Understanding trusted sources of health advice will allow us to identify community members to serve as change agents for rural T2DM interventions.